100 YEARS OF PHILOSOPHER ANTANAS MACEINA - Jovaiša, Leonas (Acta Paedagogica Vilnensia, 2008)
This article is dedicated to the most productive and profound thinker of Lithuania Antanas Maceina – in commemoration of his 100 years anniversary. He allotted the research and works for the development of personal and national education with assistance to philosophy, theology, sociology, Church, christology. Being an original thinker he expressed his views, which were not readily accepted by everybody, yet acknowledged later. He wrote many valuable works, poems among then too, on the basis of which Lithuanian Scientists of Education, philosophers, writers have been educating themselves fill now. A. Maceina lived in Lithuania and Germany during 1909–1987. His grave is in Brebersdorf, Germany.